Meta Ethics: How Ignoring Stakeholder Interests Endangers Meta/Facebook - Herman, Bill D. (Journal of Leadership, Accountability and Ethics, 2022)
The strategic wing of stakeholder theory argues that companies should seek to make decisions that are beneficial to stakeholders, especially those that can impact the firm’s bottom line. Recent revelations show Meta/Facebook’s internal deliberations are consistent with their external behavior; the firm consistently chooses to prioritize short-term financial gain over long-term relationships with stakeholders such as users, the public, employees, and policymakers. This article discusses each of these relationships. It identifies how Meta’s pattern of willfully harming all these groups creates a series of threats to the company’s long-term future. These threats include user disengagement; decreased desirability as a place of employment, leading to potential erosion of the quality of the user experience and additional user disengagement; and fueling political movements toward stronger internet regulations.